DEREGULATED EXPRESSIONS OF MYC ALTER THE EXPRESSIONS OF tRNAS IN BREAST CANCER CELLS - Pervin Elvan Tokgün; Onur Tokgün (Sabiad)
Objective: The protein synthesis process is started with DNA being transcribed into mRNA in the nucleus, then mRNA is transported to the cytoplasm and attaches to a ribosome in order to be translated into a protein. Protein synthesis not only occurs in the cytoplasm. Mitochondria by itself also has its own genetic system. Therefore mtDNA can be replicated, transcribed, and translated. MYC oncogene drives the generation of many cancer types. MYC also controls some target genes related to ribosome biogenesis and protein synthesis. Increased expressions of tRNA synthetases have been found to be important players in promoting tumor growth in various types of human cancers. In this study we aimed to identify deregulated expressions of tRNAs that are players both in the nucleus and mitochondria in a MYC-dependent manner in breast cancer cells. Material and Methods: Cells were infected with lentiviral MYC shRNA/ overexpression vectors in order to manipulate MYC expressions. TRIZOL reagent was used for RNA isolation and libraries were generated for sequencing. The quality of the RNA samples and libraries was assessed using Agilent BioAnalyzer. Sequencing was performed on the Illumina HT2500 platform. Results: We obtained 6 nuclear-encoded mitochondrial tRNAs and 65 nuclear tRNAs as a result of deregulated expression of MYC. Conclusion: This study reveals MYC-dependent regulation of tRNAs in breast cancer. Further functional studies are required for underlying molecular mechanisms.